2003
DOI: 10.1073/pnas.0436286100
|View full text |Cite
|
Sign up to set email alerts
|

Epitope and isotype specificities of antibodies to β-amyloid peptide for protection against Alzheimer's disease-like neuropathology

Abstract: Transgenic PDAPP mice, which express a disease-linked isoform of the human amyloid precursor protein, exhibit CNS pathology that is similar to Alzheimer's disease. In an age-dependent fashion, the mice develop plaques containing ␤-amyloid peptide (A␤) and exhibit neuronal dystrophy and synaptic loss. It has been shown in previous studies that pathology can be prevented and even reversed by immunization of the mice with the A␤ peptide. Similar protection could be achieved by passive administration of some but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
310
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(348 citation statements)
references
References 25 publications
33
310
1
1
Order By: Relevance
“…Recent studies report the success of both active and passive vaccination approaches to slowing and/or reversing the aggregation process, and its pathological consequences, in mouse models of light chain amyloidosis [71], Alzheimer's disease [77,79,80,[86][87][88][89][90] and mammalian prion diseases [76,[91][92][93]. The molecular mechanisms by which antibodies act in a therapeutic manner are just beginning to be understood (for recent reviews see [94][95][96][97][98][99]) (Textbox 3).…”
Section: Therapeutic Reagentsmentioning
confidence: 99%
“…Recent studies report the success of both active and passive vaccination approaches to slowing and/or reversing the aggregation process, and its pathological consequences, in mouse models of light chain amyloidosis [71], Alzheimer's disease [77,79,80,[86][87][88][89][90] and mammalian prion diseases [76,[91][92][93]. The molecular mechanisms by which antibodies act in a therapeutic manner are just beginning to be understood (for recent reviews see [94][95][96][97][98][99]) (Textbox 3).…”
Section: Therapeutic Reagentsmentioning
confidence: 99%
“…This AN-1792 clinical trial was halted due to the development of meningoencephalitis in a small proportion of the subjects [21][22][23][24][25][26], but follow up studies have demonstrated that strong anti-Aβ antibody responses specific to the linear Aβ [1][2][3][4][5][6][7][8] peptide [27] in some patients reduced AD pathology and diminished the cognitive decline associated with the disease [24,[27][28][29][30][31][32][33]. These data along with preclinical studies demonstrated that anti-Aβ antibodies directed to N-terminal region of Aβ 42 are effective in clearance of amyloid plaques [16,34,35]. On the contrary, the strong autoreactive Th1-type response specific to Aβ is thought to underlie the development of meningoencephalitis observed in the AN-1792 trial [30,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other antibodies that are specific to the C-terminus of Ab 42 do not inhibit the aggregation [163], contrary to V31-1. Altogether, these observations suggest that V31-1 binds to an epitope that is not recognised by conventional antibodies because it is less immunogenic or less accessible.…”
Section: Generation Of Ab Specific Nanobodiesmentioning
confidence: 85%